Association between fast-food outlet exposure and Body Mass Index in 124, 286 Lifelines participants. (13th November 2019) - van Erpecum, C L; van Zon, S K R; Bültmann, U; Smidt, N
Abstract: Background: Elevated Body Mass Index (BMI) is a key risk factor for numerous non-communicable diseases, such as cardiovascular diseases, cancer, diabetes type II and dementia. Previous studies showed associations between fast-food outlet exposure and BMI, but contained methodological shortcomings. Particularly within the Netherlands, evidence is scarce. We aimed to examine the association between fast-food outlet exposure and BMI among the Dutch adult general population, and whether this association was mediated by daily caloric intake. Methods: Cross-sectionally linking baseline adult data (N = 124, 286) from the Lifelines cohort to fast-food outlet location (LISA: employer register) data, we regressed fast-food outlet density (within distances of 500 metre(m), and 1, 3, and 5 kilometre (km)) and fast-food outlet proximity around participants' residential address on BMI. We used multilevel regression and multilevel mediation models, adjusting for age, sex, partner status, education, employment, neighbourhood deprivation and neighbourhood address density. We stratified analyses for urban and rural areas, as these involve different living environments and study populations. Results: More than half (56%) of participants was overweight (BMI ≥ 25.0). The average BMI in urban and rural areas was 25.9 (SD 4.4) and 26.3 (SD 4.3), respectively. In rural areas, having at least three fast-food outlets within 500 m was associated with higher BMI (B = 0.17, 95% confidence interval (CI): 0.06, 0.28). In urban areas, having at least five fast-food outlets within 1 km was associated with higher BMI (B = 0.42, 95% CI: 0.20, 0.63). Having the nearest fast-food outlet within 100m was associated with higher BMI (B = 0.43, 95% CI: 0.19, 0.67). The associations were partly explained by daily caloric intake. Conclusions: Fast-food outlet exposure may be an important environmental determinant of BMI. Policy-makers should consider intervening upon the fast-food environment. Key messages: Fast-food outlets within 500 metres in rural areas and 1 kilometre in urban areas may play a fundamental role in the rise of BMI. Targeting fast-food outlets may be key to reduce BMI on a population level.